RESULTS OF NEW TRENDS OF POTATO BREEDING PROGRAMS DEVELOPED IN RUSSSIA - & et al., Simakove (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The article presents the results of introgression of valuable genes from wild and cultivated species of Solanum and varieties of the world collection (CIP) to selection varieties in the production of backcross hybrids, selection of recombinants in backcross generations and in offspring from crossbred crosses among themselves, as well as special parent lines for implementation of programs in various areas of potato breeding. Studies were conducted to determine the effectiveness of different types of crossing during backcrossing in the frequency of occurrence of recombinant forms with high rates of polygenic traits in the hybrid progeny. Hybrids-backcrosses for immunity to virus Y, field resistance to late blight and resistance to the pathogen Ro1 of the golden potato nematode were evaluated by the method of artificial infection in pot-plant in a greenhouse. Analysis of hybrid progeny for starch content and suitability for processing by the color of chips was carried out under laboratory conditions. According to the results of the analysis of the pedigrees of 10 varieties of potato originating from the two forms of S. chacoense, a high efficiency of recurrent accumulation crosses providing introgression of the dominant immunity genes to the virus Y is revealed, as well as resistance to alternaria, heat and drought. Medium-late varieties with high field resistance of leaves and tubers were created on the basis of unstable to the late blight hybrid (F1 S. chacoense 55 d x Agra) and 3 recurrent crosses. In this case, varieties with medium field resistance to late blight participated in backcrossing. When assessing the collection of wild species for resistance to the pathogen Ro1 of the golden potato nematode, only one new source of S. chacoense 58 d was detected. Analysis of the cleavage in resistance to nematode among populations from the crossing of three-species hybrids (vrn x chc) x tbr and backcross hybrids (vrn x chc) x tbr2 confirmed control of the trait by one dominant gene, which facilitates selection for this feature. Based on the analysis of the frequency of occurrence of hybrids with different starch content in the fissile offspring, it is established that this feature is controlled by a small amount of pure additively acting genes. In the hybrid populations studied, the symmetrical frequency distribution, the presence of transgressions, and the high correlation between the average starch content of parental forms and the average offspring were observed. In a comparative assessment of 36 hybrid populations on the suitability for processing for potato products, methods for selecting parental forms for crossing and timing of the evaluation of the trait in different periods of tuber storage have been identified. Twenty-two hybrids are identified that are suitable for processing during the entire storage period without reconditioning. An increase in the efficiency of the selection process was noted in the repeated use of identical hybrid populations for selection in various environmental and geographical conditions, which significantly reduces the financial costs of creating a variety.